El concepto de razones humanitarias en el procedimiento de indulto de la Asamblea Nacional - Altamirano Burbano, Indhira Kapuzine (2016)
The pardon is an authority, that is exercised by the constitutional President of the Republic and this discretional authority may be a possible violation of fundamental rights and international standards of immediate application, hence the institution of pardon can bring many consequences to the application of justice, this occurs when that power is exercised arbitrarily. In the universal law, as well as in the Ecuadorian legislation, there are several legal ways to terminate a criminal proceeding or extinguish a sentence, including among others the pardon process. The focus of this research paper lies on pardon, which must meet certain requirements to be appropriate and accepted, the author is mainly concentrated on the study of pardon granted purely for humanitarian reasons. Humanitarian reasons could be no familiar relations in Ecuador, physical or psychological problems, incurable diseases or for any other reason that may justify awarding this benefit to the accused or convicted, who in order no longer has to bear the consequences of a penalty. However the institution of the pardon, has caused several problems or conflicts among law experts, they point out that the pardon can be a way to benefit a person who has a health problem and because of that the committed crime is left unpunished. Also it is feared that an offender who is pardoned may, at some point, could be engaging in another crime and affect society, but also the humanitarian reasons and the intention of the pardon to benefit people that through their life conditions are no longer able commit to an offense and just want to spent their last days in freedom, should be considered. Bearing the above in mind, this thesis develops a critical analysis regarding the institution of the pardon, and its advantages and disadvantages considering the given cases, both the executive and the legislature, in relation to the fundamental rights are analyzed.